1992
DOI: 10.1080/02626669209492586
|View full text |Cite
|
Sign up to set email alerts
|

Urban snowmelt and runoff in northern Sweden

Abstract: Snowmelt and runoff in urban areas in Luleà, north Sweden, are discussed and compared with rural conditions. The uneven snow distribution in cities is quantified. Energy fluxes at the snow surface in different environments are estimated. It is shown that, mainly because of increased absorbed radiative energy in the snow, the daily melt is about 10 mm higher in the city than in rural environments. In the course of prolonged snowmelt, the infiltration capacity of most soils in urban areas becomes so reduced that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 9 publications
3
69
0
Order By: Relevance
“…Xu & Buttle (1987) reported that net radiation in a Canadian suburb could be enhanced by between 67 and 435% resulting in higher intensity melt rates. Results obtained in Sweden show a similar pattern with increases of 10 to 100 W itf 2 (Bengtsson & Westerstrôm, 1992).…”
Section: Urban Energy Balancesupporting
confidence: 67%
See 4 more Smart Citations
“…Xu & Buttle (1987) reported that net radiation in a Canadian suburb could be enhanced by between 67 and 435% resulting in higher intensity melt rates. Results obtained in Sweden show a similar pattern with increases of 10 to 100 W itf 2 (Bengtsson & Westerstrôm, 1992).…”
Section: Urban Energy Balancesupporting
confidence: 67%
“…Several urban snow hydrology investigations were undertaken in Luleâ during the early to mid-1980s. These have been reported by Bengtsson (1983), Westerstrôm (1984) and Bengtsson & Westerstrôm (1992). The present study was based on climatic and snow data for four weeks during 1980 (31 March-27 April).…”
Section: Model Validation Study Site: Luleâmentioning
confidence: 99%
See 3 more Smart Citations